KINERJA MANAJEMEN OPERASIONAL DAYA TARIK WISATA TANAH LOT DALAM MENGHADAPI SITUASI PANDEMI COVID-19 - Sabadtian, Zaren Azary; Wijaya, Komang Adi Sastra; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER; Vol 2 No 2 (2022): Administrasi Publik 2022, 2023)
In 2020, the maintainability of the world of tourism faces a issue, to be specific the flare-up of the Covid-19 Infection Widespread. The Covid-19 widespread has hampered nearly all excercises carried out by the community. Tourism is one of the segments most influenced by the Covid-19 infection. One of the locales that depends on the tourism segment as a job for its individuals is the Area of Bali. One of the traveler attractions in Bali that has moreover been influenced by the episode of the Covid-19 infection is Tanah Parcel. this can be certainly a challenge for the Operational Management of the Tanah Lot Visitor Fascination to preserve the supportability of the Tanah Lot Tourism Protest in arrange to outlive the issues caused by the Covid-19 Infection.The reason of this consider was to decide the execution of the Operational Administration of Tanah Lot Traveler Fascination in Confronting the Covid-19 Widespread Circumstance. The hypothesis utilized is the Execution hypothesis of Dwiyanto, which contains 5 (five) pointers, to be specific Efficiency, service Quality, Responsiveness, Obligation, and Responsibility. This ponder employments a subjective strategy with a clear approach with information collection procedures within the frame of perception, interviews, and documentation ponders. The comes about of this consider are that the Operational Administration Execution of Tanah Lot Tourism Fascination has been going well but the comes about are not however ideal since the advancements carried out need development.   Keywords: Covid-19, Performance, Tanah Lot, Operational Managemet of DTW Tanah Lot